Pengaruh Work-Family Conflict Terhadap Turnover Intention dengan Burnout Sebagai Variabel Pemoderasi - Putra, A. A. Ngr Gde Punia Artawan; Putra, I Nyoman Wijana Asmara (E-Jurnal Akuntansi; Vol 32 No 3 (2022)DO - 10.24843/EJA.2022.v32.i03.p07, 2022)
This study aims to determine work-family conflict and burnout can affect turnover intention with burnout being the moderating variable. The location of the research was carried out in all Tax Consultant Offices in Bali. The population of confirmed tax consultant employees is 335 people by taking a sample of 77 using purposive sampling method. The study used primary data obtained from questionnaires distributed to each respondent and then regression was performed using moderate regression analysis (MRA). The results of data processing show that the work-family conflict and burnout variables have a positive effect on turnover intention, and burnout is able to moderate and strengthen the influence that occurs between work-family conflict on turnover intention. Keywords: Work-Family Conflict; Burnout; Turnover Intention.